Anxiety, depression and autonomy–connectedness: The mediating role of alexithymia and assertiveness. (24th October 2015) - Rutten, Elisabeth A. P.; Bachrach, Nathan; van Balkom, Anton J. L. M.; Braeken, Johan; Ouwens, Machteld A.; Bekker, Marrie H. J.
Abstract : Objective: Autonomy–connectedness (self‐awareness, sensitivity to others, and capacity for managing new situations) reflects the capacity for self‐governance, including in social relationships. Evidence showed that autonomy–connectedness is related to anxiety and depression. Little is known about the underlying mechanisms. We hypothesized that alexithymia and assertiveness would mediate the relationships between autonomy–connectedness and anxiety and depression. Method: Relationships among the variables were investigated in 100 patients with a mean age of 42.2 suffering from anxiety and/or depression using a cross‐sectional design. Results: The relationship between self‐awareness and both anxiety and depression was mediated by alexithymia. For anxiety, there was also a direct effect of sensitivity to others that was not explained by either alexithymia or assertiveness. Assertiveness did not have any mediational effect. Conclusions: The results indicate that particularly alexithymia explains the association of autonomy–connectedness with anxiety and depression. Practitioner points: The study confirmed the relevance of autonomy–connectedness in anxiety and depression. In treating symptoms of anxiety, it is advisable to give attention to normalizing the patient's sensitivity to others. Treatment of patients with symptoms of anxiety and depression should include assessment of emotional awareness and, in the case of impaired emotional awareness, should be tailored as to promote increased awareness.